Influence Of Work Environment, Organizational Culture And Motivation On The Performance Of Employees Of Bank Yudha Bhakti Main Branch Jakarta - Fadlan, A.Fauzan (Riviera Publishing, 2022)
This study aims to determine the effect of the work environment, organizational culture and motivation on employee performance at Bank Yudha Bhakti Main Branch Jakarta. This study uses a quantitative approach and uses primary data through distributing questionnaires to employees of Bank Yudha Bhakti Main Branch Jakarta. The population in this study were 80 respondents with a sampling technique using simple random sampling with Likert scale measurements. The data is processed through SPSS version 19.0 program with multiple linear regression analysis technical. From the results of the t test, it proves that partially the work environment has no effect on employee performance with a significance value of 0.113 > 0.05, organizational culture has no effect on employee performance with a significance value of 0.640 > 0.05, while motivation has a significant effect on employee performance as indicated by the acquisition value. significant 0.000 > 0.05. Then the results of the F test prove that the work environment, organizational culture and motivation simultaneously have a significant effect on the performance of the employees of Bank Yudha Bhakti Main Branch Jakarta with a significance value of 0.000 < 0.05. The magnitude of the contribution of all independent variables simultaneously to the dependent variable is 67.4%, while the remaining 32.6% is influenced by other variables not examined.